2012
DOI: 10.1002/anie.201207073
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of a Rhodium Peroxido Complex by Formate Derivatives: Mechanistic Studies and the Catalytic Formation of H2O2 from O2

Abstract: Hydrogenation of dioxygen: The rhodium peroxido complex 1, which can be prepared from 2 and dioxygen, can be reduced with dihydrogen sources to yield hydrogen peroxide. In a catalytic experiment, hydrogen peroxide is produced from dioxygen and ammonium formate under ambient conditions in the presence of 1 (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 142 publications
2
20
0
Order By: Relevance
“…Treatment of late transition‐metal complexes with dioxygen often give peroxido complexes, which can act as key intermediates in the conversion of organic compounds 1k. 2 At rhodium, the oxygen atoms of the peroxido ligand are often nucleophilic 2a,c. 3 Thus, a reaction of trans ‐[Rh(O 2 )(4‐C 5 NF 4 )(CN t Bu)(PEt 3 ) 2 ] ( 1 a ) with formic acid yields initially the rhodium hydroperoxido complex trans ‐[Rh(OOH){OC(O)H}(4‐C 5 NF 4 )(CN t Bu)(PEt 3 ) 2 ] at low temperatures 2c.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment of late transition‐metal complexes with dioxygen often give peroxido complexes, which can act as key intermediates in the conversion of organic compounds 1k. 2 At rhodium, the oxygen atoms of the peroxido ligand are often nucleophilic 2a,c. 3 Thus, a reaction of trans ‐[Rh(O 2 )(4‐C 5 NF 4 )(CN t Bu)(PEt 3 ) 2 ] ( 1 a ) with formic acid yields initially the rhodium hydroperoxido complex trans ‐[Rh(OOH){OC(O)H}(4‐C 5 NF 4 )(CN t Bu)(PEt 3 ) 2 ] at low temperatures 2c.…”
Section: Methodsmentioning
confidence: 99%
“…2 At rhodium, the oxygen atoms of the peroxido ligand are often nucleophilic 2a,c. 3 Thus, a reaction of trans ‐[Rh(O 2 )(4‐C 5 NF 4 )(CN t Bu)(PEt 3 ) 2 ] ( 1 a ) with formic acid yields initially the rhodium hydroperoxido complex trans ‐[Rh(OOH){OC(O)H}(4‐C 5 NF 4 )(CN t Bu)(PEt 3 ) 2 ] at low temperatures 2c. Subsequently, hydrogen peroxide and the rhodium(I) complex trans ‐[Rh(4‐C 5 NF 4 )(CN t Bu)(PEt 3 ) 2 ] ( 2 ) are furnished.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthy is that complex 2 is one of the few examples of a s-bound trifluoropropynyl ligand at ac omplexo fatransition metal. The 31 P{ 1 H} NMR spectruma t1 21.5 MHz discloses a system of higher order that simplifies at 242.8 MHz (see the Supporting Information), although it still represents aspectrum of highero rder.T oo btain the coupling constants, the spectrum of 2 was simulated [15] (Figure 1) to be an A 2 BMX 3 spin system.T wo resonances in a1:2 ratio at d = 20.5 and 19.1 ppm are observed that have rhodium-phosphorus coupling constants typical for rhodium(I) complexes( J = 128.9 and1 34.8 Hz, respectively), [16] and the coupling constantb etween the phosphorusn uclei is J = 39.4 Hz. [14a-f] Complex 2 shows am olecular ion peak at m/z = 550 by liquid injection field desorption/ionizationm asss pectrometry (LIFDI-MS).…”
Section: Resultsmentioning
confidence: 99%
“…The crystallographic data and spectral features of 4 are consistent with those of related Rh III (η 2 -O 2 ) complexes. 5,34,39,40 The X-ray crystal structure of 4b, which is provided in Figure 3 Inorg. Chem.…”
Section: ■ Resultsmentioning
confidence: 99%